"Don't Worry, it's Just a Girl!": Negotiating and Challenging Gendered Assumptions in Sydney's Breakdancing Scene. (3rd July 2016) - Gunn, Rachael
Abstract : In this article, I analyse how bodily potential is culturally regulated in Sydney's breakdancing (breaking) scene through drawing both on my breakdancing practice and interviews conducted with prominent figures in this scene. I critically examine my lived experiences as one of only a few female breakdancers ("b-girls") in Sydney through analytic autoethnography, and use the theoretical tools of Deleuze and Guattari to unpack and challenge normative gendered narratives. With breakdancing culturally inscribed as masculine ("b-boying") and its conventions interlocking with broader patriarchal restrictions that inhibit female participation and bodily expression, I argue that the Sydney breaking scene is both a site of transgression and regression for the female body. This paradox confronting the b-girl sees her participation as "othered", while also challenging normative assumptions of gender. Through situating specific practices of breaking within broader Australian culture and gender norms, I examine how the performances of b girls and b-boys in Australia disrupt the stability of binary logic on which the organization of bodies is so heavily reliant and, in doing so, allow for the experience of breaking as a site of "pure" difference.